LA PREVENCIÓN DE LAS MANIFESTACIONES DE ALCOHOLISMO EN LA EDUCACIÓN TÉCNICA Y PROFESIONAL: THE PREVENTION ALCOHOLISM MANIFESTATION IN THE TECHNICAL AND PROFESSIONAL EDUCATION - Silva Trujillo, Alexey; Ávila Cutiño, Yaritza (Opuntia Brava, 2018)
En el presente artículo se brindan acciones educativas concretas para la prevención del alcoholismo en el proceso de educación para la salud, dirigidas a potenciar la formación integral de los estudiantes en el proceso de enseñanza-aprendizaje de la Química en la Educación Técnica Profesional para fortalecer su conducta y capacitarlos para el porvenir. ABSTRACT In the present article educative actions are offered directed to the prevention of alcoholism in the process for health education, devoted to upgrade the integral formation of the students in the teaching-learning process of Chemistry in the technical and professional education to strengthen their future behavior and capacities. KEY WORDS: prevention, alcoholism, behaviour.